Rachid Taha and the Postcolonial Presence in French Popular Music - Stratton, Jon (Intellect, 2013)
This article considers the work of Rachid Taha from a postcolonial perspective. Taha is the most well-known French Algerian musician working in popular music in France and now has a considerable following in the anglophone world. The article is most concerned with the ways Taha's music expresses the experience of being identified as neither French nor Algerian while also feeling that both heritages are central to his identify as a Beur. The article focuses specifically on an understanding of Taha's work in terms of metissage, hybridity. Taha's first group was Carte de Sejour. Starting from a track on their first album, Rhorhomanie, which uses phrases from Arabic, French and English, the article goes on to examine examples of recordings where Taha has offered a revisioning of already well-know songs: Carte de Sejour's version of Charles Trenets 'Douce France'/'Sweet France', Taha's version of Dahmane el Harrchie's 'Ya Rayah' and, finally, Taha's version of the Clash's 'Rock the Casbah'.